THE IMPACT OF POOR RELATIONSHIPS AND PARENTING TYPE ON CHILD'S BEHAVIOR AND LEARNING MOTIVATION - Zulfariati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This article aims at describing the bad effects of bad parenting at home and bad relationship of parents with the son towards the son’s behavior and his learning motivation. By using the interviewing one of the teenagers during the recent three years, it can be described how was the effects of the authoritarian parenting style towards the son’s behavior and learning motivation. Authoritarian parenting style and bad relationship of parents and the son disturb the son’s five individual basic psychological needs as stated by Maslow: 1) safety, 2) love, 3) belongingness, 4) respect, and 5) self-esteem. It should be emphasized that these basic needs are essentially unconciuous, and when they are not filled, one’s behavior is more or less dominated by the drive to fill them. It results deficiency-motivated behavior, effects one’s basic anxiety, which then put him in the vicious circle. It increased bad behaviours in form of bad language use, conflicts, and neurotic needs. Naturally each individual has basic needs that should be fulfilled in order to make him have good behaviour and high motivation to learn both at home and school.